In vivo vaccination with cell line-derived whole tumor lysates: neoantigen quality, not quantity matters - Salewski, Inken; Gladbach, Yvonne S.; Kuntoff, Steffen; Irmscher, Nina; Hahn, Olga; Junghanß, Christian; Maletzki, Claudia (Journal of translational medicine, 2020)
Cancer vaccines provide a complex source of neoantigens. Still, increasing evidence reveals that the neoantigen quality rather than the quantity is predictive for treatment outcome.
Gesehen am 30.11.2020